Penerapan Teileren Method Terhadap Pembelajaran Al-Qur’an Hadis Di Kelas XI MAN 2 AGAM - Dyna Aulya Zuliarti; Fauzan Fauzan (STIKes Ibnu Sina Ajibarang, 2024)
conducted research at Madrasah Aliyah Negeri 2 Agam which was motivated by the implementation of the Teileren Method (partial method) which was not yet appropriate or optimal carried out by the teacher. This research aims to describe the application of the Teileren Method (part method) to the Learning of Al-Qur'an Hadith in Class XI MAN 2 AGAM. This problem is researched using descriptive qualitative research methods which are aimed at describing and analyzing the phenomenon of events, social activities, attitudes, beliefs, thoughts of people individually and in groups using the type of case study research. Data collection was carried out using observation, interviews and documentation techniques. The key informants in this research were Al-Qur'an Hadith teachers and class XI students at Madrasah Aliyah Negeri 2 Agam. To analyze the data, researchers grouped it based on existing problems. Based on the findings of research conducted by the author, the results show that: the application of the Teileren Method (part method) in learning Al-Qur'an Hadith in class XI is not completely satisfactory and has shortcomings. There are four steps in the Teileren Method (part method) in learning Al-Qur'an Hadith in class . The advantages of the teileran method in learning Al-Quran Hadith itself are that it makes it easier for students to memorize long material and memorizing does not take a long time. The disadvantages and obstacles of the teileran method itself are that it is time consuming and overwhelming when the material has been combined.